Німецькі підприємства в окупованій Україні (1941-1944 рр.) - Дубик, М.Г. (Сумський історико-архівний журнал, 2010)
The reasons and conditions of German enterprises functioning on the occupied territory of Ukraine, the process of starting and finishing their activities are analyzed in the article. The data on the quantity of enterprises according to the branches and most outstanding German firms is given.